Financial sustainability for nonprofit organizations : a review of the literature - Sontag-Padilla, Lisa M.; Staplefoote, Lynette; Morganti, Kristy Gonzalez (RAND, 2012)
Nonprofits face a myriad of challenges in establishing and maintaining financial sustainability, and these challenges are exacerbated for nonprofits serving low-resources, high-need communities. This literature review identifies key themes and findings that may inform operations and decisionmaking related to improving sustainability in such organizations. The authors conducted systematic literature searches using a combination of academic search engines and the broader Internet. They identify and discuss key challenges of financial sustainability for nonprofits, such as over-reliance on external funding sources, demonstrating value and accountability to funders, and promoting community engagement and leadership, as well as promising practices for meeting these challenges and achieving financial sustainability. Additionally, the authors discuss unique challenges faced by nonprofits serving low-resources, high-need populations. It is the authors' hope that this review will enhance the limited literature on financial sustainability in low-resource or high-need communities and will contribute to an evidence base for promising practices, providing leaders of and investors in nonprofits the ability to support and promote growth among organizations serving those most in need.